Educational pairings and fertility across Europe: How do the low-educated fare? - Natalie Nitsche; Anna Matysiak; Jan Van Bavel; Daniele Vignoli (Comparative Population Studies (CPoS), 2021)
Recent research suggests that the fertility-education relationship may be mediated by the educational attainment of the partner, especially among the tertiary-educated. However, there are no studies focusing on the couple-education-fertility nexus among couples who achieved only basic educational attainment, even though resource pooling theory predicts differences in family formation by couples' joint levels of socio-economic resources. We address this research gap and investigate how educational pairings among married and cohabiting partners relate to second and third birth transitions across 22 European countries, using data from the EU-SILC (European Union Statistics on Income and Living Conditions) panel and discrete time event history models. Our findings show significantly lower second and third birth transition rates among homogamous low-educated couples compared to heterogamous couples with one low- and one medium or highly-educated partner in the Nordic countries, but not across the rest of Europe. However, couples with one or two low-educated partners have significantly lower second birth rates compared with couples with two highly-educated partners in all European regions.
urn:nbn:de:bib-cpos-2021-19en5
Keywords: 300; Couples; Education; Europe; Fertility; Second birth